2022
DOI: 10.1371/journal.pntd.0010724
|View full text |Cite
|
Sign up to set email alerts
|

Chronic sequelae complicate convalescence from both dengue and acute viral respiratory illness

Abstract: Long Covid has raised awareness of the potentially disabling chronic sequelae that afflicts patients after acute viral infection. Similar syndromes of post-infectious sequelae have also been observed after other viral infections such as dengue, but their true prevalence and functional impact remain poorly defined. We prospectively enrolled 209 patients with acute dengue (n = 48; one with severe dengue) and other acute viral respiratory infections (ARI) (n = 161), and followed them up for chronic sequelae up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Several viral infections, like Dengue fever ( 28 ), WNV ( 29 ), SARS-CoV-2 ( 30 ), EVDs ( 31 ), and Marburg viruses ( 32 ), impact the neuropsychiatric systems upon complications present PVF, which may linger for months after infection. The PVF presents similar to chronic fatigue syndrome, characterized by fatigue/weakness, headache, dizziness, musculoskeletal pain, and cognitive and sleep disorders, and could be linked to dysregulated CCM ( 33 ) and microbial dysbiosis impacting the gut–brain axis ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several viral infections, like Dengue fever ( 28 ), WNV ( 29 ), SARS-CoV-2 ( 30 ), EVDs ( 31 ), and Marburg viruses ( 32 ), impact the neuropsychiatric systems upon complications present PVF, which may linger for months after infection. The PVF presents similar to chronic fatigue syndrome, characterized by fatigue/weakness, headache, dizziness, musculoskeletal pain, and cognitive and sleep disorders, and could be linked to dysregulated CCM ( 33 ) and microbial dysbiosis impacting the gut–brain axis ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…La trombocitopenia estuvo presente en ambas patologías, pero fue más severa (<50.000/mm 3 ) en el dengue grave, lo que concuerda con un estudio realizado en pacientes con dengue e insuficiencia respiratoria, que reportó trombocitopenia grave en el 82,61% de los casos de pacientes con dengue grave (Kalimuddin et al, 2022) y similar a lo encontrado en otro estudio en Pakistán, donde los pacientes con dengue grave tenían trombocitopenia y plaquetas significativamente más bajas que los casos con dengue no grave (Arshad et al, 2022) hallazgo que también fue reportado en pacientes que además presentan linfohistiocitosis (Acharya et al, 2022). Esto contrasta con el estudio realizado en Puerto Maldonado, Perú, donde el recuento de plaquetas de los pacientes con dengue grave se encontraba dentro de los rangos normales, excepto en el grupo de 10 a 19 años que se encontraban por debajo de 150.000/mm 3 (Rojas et al, 2015).…”
Section: Discussionunclassified
“…Although there is currently no evidence that COVID-19 requires treatment during the recovery phase, experts have called for research to identify appropriate therapies such as vaccines and antiviral drugs to prevent sequelae ( Kalimuddin et al, 2022 ). Studies have also analyzed pharmacological treatment in the recovery phase and found that it is mainly symptomatic supportive therapy, while the use of antibiotics and antivirals is ineffective ( Liu et al, 2020 ).…”
Section: Potential Advantages Of Traditional Chinese Medicine In the ...mentioning
confidence: 99%